Peran Humas Pemerintah Kota Surabaya Dalam Membangun Citra Bangga Surabaya - Jurnal Governance Jurnal Kebijakan & Manajemen Publik (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2020)
Public Relations cannot be separated from involvement in Government Institutions. Public relations within the government has a very strategic function in an effort to improve the image of the government. The purpose of this study is to describe the role of the Surabaya City Government public relations in developing the Proud Image of Surabaya and its success in the community. The research approach is qualitative research. Data collection techniques using interviews, observation and documentation. And data analysis techniques are data collection, data reduction, data presentation and verification or drawing conclusions so that the data collected is good enough to be used as material for scientific work.The results showed that the role of Communicator public relations through Electronic Media on Websites, and Social Media through Twitter, Facebook, Instagram, Youtube and Podcast, Print Media through Press Release and Gapura Magazine, and Oral Media through Press Conference and Press Interview. Relationship fostering good relations or cooperation with internal parties by establishing relations between sub-sections in public relations and establishing relationships between Regional Apparatus Organizations, and fostering good relations or cooperation with External parties by establishing relations with the media and establishing relations with the public. Back up Management supports the management of the Surabaya City Government and disseminates the activities and programs of the Surabaya City Government. Good Image Maker Minimize negative issues of the Surabaya City Government, Publish Positive News about the Surabaya City Government, and Reputation or awards. And the success of public relations in building the image of Proud of Surabaya in the community in the Knowledge or Understanding of the community towards Proud of Surabaya and Participation or community involvement in maintaining Proud of Surabaya. The suggestion is that public relations should continue to maintain its good performance and continue to improve its performance as a Communicator, Relationship, Back up Management and Good Image Maker and improve the quality of communication by socializing Proud Surabaya through Regional Apparatus Organizations in programs or activities in the Government.